2012
DOI: 10.1093/hmg/dds139
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-regulated processing of the oncomir MiR-27a, which targets Prohibitin in prostate cancer

Abstract: MicroRNAs (miRs) play an important role in the development of many complex human diseases and may have tumour suppressor or oncogenic (oncomir) properties. Prostate cancer is initially an androgen-driven disease, and androgen receptor (AR) remains a key driver of growth even in castration-resistant tumours. However, AR-mediated oncomiR pathways remain to be elucidated. We demonstrate that miR-27a is an androgen-regulated oncomir in prostate cancer, acting via targeting the tumour suppressor and AR corepressor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 51 publications
5
101
1
4
Order By: Relevance
“…94 Moreover, the androgen receptor, an important tumorigenic player in prostate cancer, induces the transcription of miR-23a, miR-27a and miR-24-2, but more significantly accelerates primiR-23a/27a/ 24-2 cluster processing. The evidence indicates that primiR-23/27/24 cluster is regulated by hormone signaling in different cancers, which highlights its potential implication in the therapeutic area as a new drug target 95 (Fig. 2B).…”
Section: Drosha Processing and Alterations In Cancermentioning
confidence: 82%
“…94 Moreover, the androgen receptor, an important tumorigenic player in prostate cancer, induces the transcription of miR-23a, miR-27a and miR-24-2, but more significantly accelerates primiR-23a/27a/ 24-2 cluster processing. The evidence indicates that primiR-23/27/24 cluster is regulated by hormone signaling in different cancers, which highlights its potential implication in the therapeutic area as a new drug target 95 (Fig. 2B).…”
Section: Drosha Processing and Alterations In Cancermentioning
confidence: 82%
“…12 However, Fletcher et al reported that AR could also downregulate PHB through increasing miR-27a expression, suggesting that AR may inhibit its own repressor PHB in a negative feedback loop. 13 Therefore, accumulating evidences support the fact that PHB acts as a potent transcriptional co-repressor of ERa in the breast cancer cells and AR in the prostate cancer cells. However, little is known regarding the role of PHB and whether PHB could regulate AR expression in the ER-positive breast cancer.…”
Section: Introductionmentioning
confidence: 98%
“…За послед-ние годы проведен ряд исследований изменения про-филя экспрессии микроРНК в клетках РПЖ [26][27][28], что позволило продемонстрировать роль микроРНК в опосредовании проканцерогенных эффектов андро-генов [29]. В частности, среди андроген-регулируемых микроРНК участие в поддержании опухолевого роста в клетках предстательной железы экспериментально доказано для miR-21 [30], miR-125b [31], miR-141 [29,32], miR-27a [33]. Например, повышенный уровень miR-21 приводит к активации пролиферации клеток РПЖ как при сохраненной андрогенной стимуляции, так и после прекращения таковой [30].…”
Section: том 2 обзорные статьиunclassified
“…С другой стороны, введение в AR-негативные клетки РПЖ (линия PC-3) синтетической копии miRNA-21 активировало продукцию клетками AR (мРНК и белок) и позволяло наблюдать эффекты активации этих рецепторов (усиление синтеза про-статспецифического антигена). Аналогичный феномен «взаимостимуляции» AR и miRNА-27а был описан в исследовании C. E. Fletcher et al [33]. В обоих случа-ях исследователи предполагали, что микроРНК сти-мулирует транскрипцию AR опосредованно -путем посттранскрипционного угнетения экспрессии фак-торов, ингибирующих синтез AR (miRNA-21 / PTEN; miRNA-27a / PHB).…”
Section: том 2 обзорные статьиunclassified
See 1 more Smart Citation